Long Time-delay Control of Cement Slurry Density Based on Smith-fuzzy PID Decoupling - Li Yong; Fan Heng; Ji Yu; Cheng Sida; Meng Jiansheng (Shiyou jixie)
The cement slurry mixing system has the characteristics of nonlinearity，time variation and long time-delay， which make it impossible to achieve stable and accurate control of automatic cementing devices by traditional techniques. This paper presents an advanced strategy of control based on Smith predictive compensation and fuzzy PID decoupling（Smith-fuzzy PID decoupling）.Firstly， through the mathematical modeling and coupling analysis of the cement slurry mixing system， the feedforward compensator was used to compensate for the possible disturbances in the system in advance， which effectively reduces the coupling effect. Then， the Smith-fuzzy PID decoupling controller was designed， and the PID parameters were adjusted through fuzzy logic to adapt to the nonlinear and time-varying characteristics of the system，so as to achieve accurate control of density. Finally，simulation experiments and anti-interference analysis were carried out on the Matlab/Simulink platform. The results show that compared with Smith predictive compensation and fuzzy PID control， the proposed control based on Smith-fuzzy PID decoupling is significantly superior in dynamic performance， steady-state performance and anti-interference ability， and has a strong robustness. This control strategy can effectively reduce the overshoot， speed up the system adjustment， and improve the system stability. It provides a reliable solution to the accurate control of cement slurry density， and will play a theoretical guiding role in the intelligent development of cement slurry mixing system.